Bone Marrow Transplant in Adrenoleukodystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Three children with adrenoleukodystrophy (ALD) were treated with allogeneic bone marrow transplantation (BMT) at Huddinge University Hospital, Sweden.